Bony-legs - Cole, Joanna; Zimmer, Dirk (New York : Scholastic, 1983)
When a terrible witch vows to eat her for supper, a little girl escapes with the help of a mirror and comb given to her by the witch's cat and dog
"Based on the tale 'Baba-Yaga' in Russian fairy tales by Aleksandr Afanasev"--T.p. verso
RL:2
AGES 5-8
370
370
Accelerated Reader AR
Keywords: Baba Yaga (Legendary character) -- Legends; Fairy tales; Folklore -- Russia